3rd AIAA/CEAS Aeroacoustics Conference 1997
DOI: 10.2514/6.1997-1589
|View full text |Cite
|
Sign up to set email alerts
|

Inlet shape effects on the far-field sound of a model fan

Abstract: A wind tunnel test was conducted to determine the effects of inlet shape on fan radiated noise. Four inlet geometries, which included a long standard flighttype inlet, a short, aggressive flight inlet a scarf inlet, and an elliptical inlet were investigated in the study.The fan model used in the study was a 0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…For example, as aforementioned in Sect. 1, the study presented in [7] showed that sound sideline directivity can be affected up to 8 dB by the inlet shape, and the work of [8] whose results indicated a 10 dB rise of the broadband levels when the inlet turbulence level increases from 2 to 8%. This issue was also addressed in [50], evidencing interference effects on noise measurements due to the presence of the ICD and measurement probes located upstream of the rotor.…”
Section: Comparison Of Noise Computation By Lbm and Fw-hmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, as aforementioned in Sect. 1, the study presented in [7] showed that sound sideline directivity can be affected up to 8 dB by the inlet shape, and the work of [8] whose results indicated a 10 dB rise of the broadband levels when the inlet turbulence level increases from 2 to 8%. This issue was also addressed in [50], evidencing interference effects on noise measurements due to the presence of the ICD and measurement probes located upstream of the rotor.…”
Section: Comparison Of Noise Computation By Lbm and Fw-hmentioning
confidence: 96%
“…Nonuniform inflow can be produced by many different factors such as position of the temperature sensor at the inlet, turbulent boundary layer on the casing wall, atmospheric turbulence, inclined inflow due to inclination of the fan axis relative to the flow. For example, the study presented in [7] shows that small changes of the inlet shape of the nacelle affect the sideline tonal noise level up to 8 dB. In addition, the numerical work of [8] shows that the turbulence intensity level of the incoming flow influences significantly the noise generated, as much as an increase of 10 dB when comparing the noise generated from a low turbulent inflow case with a highly turbulent inflow configuration.…”
Section: Introductionmentioning
confidence: 98%
“…With these models in hand, it is useful to compare with other experiments, certain aspects of which make their results unsuitable for model development, but which may still serve as a qualitative check on the general aspects of the model. Clark et al [28] tested a 10% scale model of the Pratt and Whitney Advanced Ducted Propeller (ADP) with several inlet shapes (short, long, scarfed, and elliptical) in the NASA Langley 14-by 22-Foot Subsonic Tunnel. The different inlet shapes caused nonuniformity of the inlet boundary layer thickness that led to unsteady forces on the fan that propagated as increased fan noise over the entire acoustic measurement region.…”
Section: Turbulence Ingestionmentioning
confidence: 99%
“…To model the higher harmonics (up to 4BPF), the noise levels are subtracted by 3 dB for each harmonic to model a decreasing effect of BLI with increasing BPF harmonic. Limited data from Jones et al [26], Clark et al [28], and Koch [29] suggest that higher harmonics are affected by nearly the same amount as the fundamental tone, but because these data are more limited and less applicable to the physical scenario at hand, the use of a 3 dB subtraction for each harmonic represents a conservative choice to predict this effect.…”
Section: Mean Flow Distortionmentioning
confidence: 99%
“…In addition to developing quieter engines and airframe systems, an approach that is considered in the design of quieter aircraft is the shielding of noise components. For example, engines can be placed above an aircraft wing or fuselage to partially shield engine noise radiation, or the lower side of the inlet of an engine can be extended forward (scarf inlet 1 ) to reflect inlet noise away from the ground. This approach to noise reduction has been the subject of growing interest [2][3][4][5][6][7] which has revealed a need for further validation and improvement of current noise scattering prediction tools.…”
Section: Introductionmentioning
confidence: 99%